Perbedaan Tingkat Stres Kebisingan pada Penderita Diabetes Mellitus dan Non Diabetes Mellitus - Fitriani, Dora; Hasneli, Yesi; Huda, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease that affects various physiological aspects, including the body's response to environmental stressors such as noise. In DM patients, the body cannot efficiently respond to blood sugar spikes, resulting in persistently high blood sugar levels (hyperglycemia), which can exacerbate physical and mental stress. This study aims to determine the differences in noise-induced stress levels between DM and non-DM patients. This study used an observational analytic design with a case-control approach. The respondents consisted of 17 DM patients and 17 non-DM patients in the working area of Simpang Tiga Public Health Center. The research samples were selected based on inclusion criteria using purposive sampling. The analysis included univariate analysis to observe frequency distribution and bivariate analysis using the Chi-Square test. Statistical tests showed a significant difference in noise-induced stress levels between DM and non-DM patients, with a p-value (0.001) < alpha (0.05). The findings indicate that DM patients experience higher levels of noise-induced stress compared to non-DM patients. Key word: Diabetes Mellitus, Noise, Stress